Corporate Governance Country Assessment : Brazil - World Bank (Washington, DC, 2012)
Brazil today is at an advanced stage in the corporate governance debate, and demand for voting shares, transparency, tag along rights, and other corporate governance rights has increased significantly. As a result, share offerings take place on the special listing segments rather than on the main board. Enforcement has improved substantially, as the securities regulator, (CVM), enforces laws and regulations in a consistent and predictable fashion. The private sector took the initiative to provide incentives that will bridge the gap between the existing legal framework and best practice for issuers who want to distinguish themselves in the competition for capital at home and abroad. The stock exchange (BOVESPA) introduced special listing segments requiring progressively stricter corporate governance standards. These have given investors a benchmark against which to measure corporate governance. CVM, BOVESPA, the Brazilian Institute of Corporate Governance (IBGC) and firms listed on the Novo Mercado have been major champions and drivers of change. The challenge now is to 'mainstream' corporate governance reform beyond this limited group of insiders and make it an integral part of the investment climate agenda.